KAJIAN PENGEMBANGAN RUANG TERBUKA HIJAU DI KOTA BANDUNG - Triyono Puspitojati; Ismayadi Samsoedin (Jurnal Analisis Kebijakan Kehutanan, 2015)
Bandung city is facing serious environmental problems. Efforts are being made to overcome these problems by developing 10 types of green open space (GOS), including demography-based green open space park (DGOSP). The objective of the study is to examine GOS and DGOSP developments. The results of the study are as follows: First, in 2004-2011, the development of GOS was 1,663 ha, which was 191 ha lower than planned area. Second, in the same period, the development of DGOSP was 101.04 ha, 2 which was 0.75 ha lower than planned area. Third, the development of non-DGOSP is varying from 0.05 m per capita in Tegallega 2 2 2 to 2.58 m per capita in Ujungberung, with an average of 0.89 m per capita. The development plan of the DGOSP is 0.91 m per capita. Fourth, The Goverment of Bandung City still needs to develop GOS of 3,108 ha in order to comply with the provision of GOS by 30%. This could be achived by increasing and incorporating GOS development funds in the city budget.